The Influence of Understanding Tax Regulations, Tax Rates and Taxpayer Awareness on Taxpayer Compliance of E-commerce Users on Online Shopping Entrepreneurs - Mandasari, Resty; Kamal, Mustafa; Helmiati, Helmiati (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aims to examine the influence of understanding tax regulations, tax rates, and taxpayer awareness on taxpayer compliance among e-commerce entrepreneurs in Bangkinang City, Indonesia. The study addresses the growing need for effective tax administration in the rapidly expanding digital economy sector. Materials and methods: A quantitative approach was employed utilizing a survey questionnaire distributed to 150 e-commerce entrepreneurs in Bangkinang City. The sampling technique used was purposive sampling with specific inclusion criteria. Data were collected between January and March 2025 and analyzed using multiple linear regression analysis. Results: The findings revealed significant positive relationships between understanding tax regulations (β = 0.412, p < 0.01), taxpayer awareness (β = 0.376, p < 0.01), and taxpayer compliance. However, tax rates showed a significant negative relationship with compliance (β = -0.298, p < 0.01). The coefficient of determination (R²) indicated that these three variables collectively explain 68.3% of the variance in taxpayer compliance. Conclusions: The study concludes that enhancing taxpayers' understanding of e-commerce tax regulations and raising taxpayer awareness are crucial strategies for improving compliance. Additionally, the negative impact of tax rates suggests that tax authorities should consider optimizing rate structures specific to e-commerce businesses to encourage compliance.